Peran Media Digital dalam Pembentukan Literasi Keagamaan Santri di Indonesia - Raharjo, Novianto (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
In the rapidly advancing digital era, traditional Islamic boarding schools (pesantren) in Indonesia face new challenges in preserving Islamic values while meeting students' needs for digital literacy. This study examines the role of digital media in shaping religious literacy among students in traditional pesantren in Indonesia. Using a literature review approach, the research aims to provide a comprehensive understanding of how digital media is utilized by students and the challenges pesantren face in maintaining Islamic values amidst the digital information flow. The study’s findings indicate that digital media presents both opportunities and challenges for pesantren. On one hand, digital media enables students to access a variety of religious information sources, enriching their knowledge. On the other hand, the ease of access to information that may not always align with Islamic teachings requires close monitoring by pesantren authorities. In this context, the roles of kyai and ustadz (religious leaders and teachers) are essential in guiding students to ensure that the digital literacy they acquire remains in harmony with the Islamic values upheld by pesantren.